Gender Differences in In-Hospital Outcome in Non STElevation Myocardial Infarction - Khan, Mohammad Anisul Goni; Hossain, Nur; Hossain, Zakir; Rahman, Md Sajjadur; Ahmed, Md Shuaib (Bangladesh Heart Journal, 2017)
Among the different types of acute coronary syndrome (ACS), non ST-elevation MI (NSTEMI) is about 25%. Women with ST-segment-elevation myocardial infarction have a worse prognosis than men. However, information about the prognosis of women with non-STEMI is scarce. There are several studies regarding gender difference in NSTEMI. Almost all of these studies were done in western & European countries. Though in third world countries like Bangladesh the patients of NSTEMI are found in large number, limited data are available in this situation. The aim of the study is to determine difference in effect between the genders, in real life patients, with non-invasive treatment. So that definite measures can be formulated to the patients properly of that gender specific group. Bangladesh Heart Journal 2017; 32(1) : 18-22